First Assessment of a Carbon Monoxide Laser and a Thulium Fiber Laser for Fractional Ablation of Skin. Issue 8 (14th January 2020) - Ha, Linh; Jaspan, Martin; Welford, David; Evers, Michael; Kositratna, Garuna; Casper, Malte Johannes; Manstein, Dieter; Birngruber, Reginald
Abstract : Background and Objectives: A recent generation of 5, 500 nm wavelength carbon monoxide (CO) lasers could serve as a novel tool for applications in medicine and surgery. At this wavelength, the optical penetration depth is about three times higher than that of the 10, 600 nm wavelength carbon dioxide (CO2 ) laser. As the amount of ablation and coagulation is strongly influenced by the wavelength, we anticipated that CO lasers would provide extended coagulation zones, which could be beneficial for several medical applications, such as tissue tightening effects after laser skin resurfacing. Until now, the 1, 940 nm wavelength thulium fiber (Tm:fiber) laser is primarily known as a non‐ablative laser with an optical penetration depth that is eight times higher than that of the CO2 laser. The advantage of lasers with shorter wavelengths is the ability to create smaller spot sizes, which has a determining influence on the ablation outcome. In this study, the ablation and coagulation characteristics of a novel CO laser and a high power Tm:fiber laser were investigated to evaluate their potential application for fractional ablation of the skin. Study Design/Materials and Methods: Laser‐tissue exposures were performed using a novel CO laser, a modified, pulse‐width‐modulated CO2 laser, and a Tm:fiber laser. We used discarded ex vivo human skin obtained from abdominoplasty as tissue samples. Similar exposure parameters, such as spot size (108–120 μm), pulse duration (2 milliseconds), and pulse energy ( 10–200 mJ) were adjusted for the different laser systems with comparable temporal pulse structures. Laser effects were quantified by histology. Results: At radiant exposures 10‐fold higher than the ablation threshold, the CO laser ablation depth was almost two times deeper than that of the CO2 laser. At 40‐fold of the ablation threshold, the CO laser ablation was 47% deeper. The ablation craters produced by the CO laser exhibited about two times larger coagulation zones when compared with the CO2 laser. In contrast, the Tm:fiber laser exhibited superficial ablation craters with massive thermal damage. Conclusions: The tissue ablation using the Tm:fiber laser was very superficial in contrast to the CO laser and the CO2 laser. However, higher etch depths should be obtainable when the radiant exposure is increased by using higher pulse energies and/or smaller spot sizes. At radiant exposures normalized to the ablation threshold, the CO laser was capable of generating deeper ablation craters with extended coagulation zones compared with the CO2 laser, which is possibly desirable depending on the clinical goal. The effect of deep ablation combined with additional thermal damage on dermal remodeling needs to be further confirmed with in vivo studies. Lasers Surg. Med. © 2020 The Authors. Lasers in Surgery and Medicine Published by Wiley Periodicals, Inc.